2021
DOI: 10.1002/cssc.202102080
|View full text |Cite
|
Sign up to set email alerts
|

Cathode Active Material Recycling from Spent Lithium Batteries: A Green (Circular) Approach Based on Deep Eutectic Solvents

Abstract: The transition to a circular economy vision must handle the increasing request of metals required to satisfy the battery industry; this can be obtained by recycling and feeding back secondary raw materials recovered through proper waste management. Here, a novel and green proof‐of‐concept was developed, based on deep eutectic solvents (DESs) to fully and easily recover valuable metals from various cathode active materials, including LiMn2O4, LiNi0.5Mn1.5O4, and LiNi0.8Co0.2O2. DES composed of choline chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 21 publications
(43 reference statements)
2
49
0
Order By: Relevance
“…[8] Morina et al reported the reuse of a DES with an organic acid as hydrogen bond donor. [4] In their work, LIBs cathode materials were leached at temperatures up to 170 °C and for 24 h. Again, in this latter works, no results about DES decomposition were reported, though Rodriguez et al demonstrated the decomposition of DESs based on organic acid at milder condition (80 °C; 2 h). [19] In this work, thermally treated DES was used in the leaching of LIBs black mass allowing for extraction yields greater than 90 % after only 4 h. Among the degradation products, the trichloride anion Cl 3…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[8] Morina et al reported the reuse of a DES with an organic acid as hydrogen bond donor. [4] In their work, LIBs cathode materials were leached at temperatures up to 170 °C and for 24 h. Again, in this latter works, no results about DES decomposition were reported, though Rodriguez et al demonstrated the decomposition of DESs based on organic acid at milder condition (80 °C; 2 h). [19] In this work, thermally treated DES was used in the leaching of LIBs black mass allowing for extraction yields greater than 90 % after only 4 h. Among the degradation products, the trichloride anion Cl 3…”
Section: Introductionmentioning
confidence: 99%
“…[2] A competitive green alternative is represented by solvometallurgical processes, where deep eutectic solvents (DESs) are used to dissolve LIB metal oxides. [3,4] DES are mixtures of two or more components with a melting point lower than those of its individual components, which include a hydrogen bond acceptor (HBA; typically a quaternary ammonium salt) and a hydrogen bond donor (HBD; e. g., alcohol or carboxylic acid). Synthesis of DESs is generally straightforward, and biodegradability, safety, and low price can be ensured by the proper selection of the DES components.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations